SYSTEMATICAL COMPARATIVE FOR TWO SPECIES AMARANTHUS albus L. AND AMARANTHUS gracilis DEFS. (AMARANTHACEAE) IN IRAQ - Aliwy, S. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study dealt with comparative taxonomic study for the two species Amarantus albus L. and Amaranthus gracilis Defs. in Iraq . It was included the important morphological characters for roots, stems, leaves ,petioles ,inflorescences and its parts ,floral parts ,fruits and seeds . Also the dimensions and properties of each part have been recorded ,even its colors which helps in isolated and diagnosed the two species, the first one recognized by its white stems while the other one had red stems, also the first species characterized by axillaries sessile inflorescences with so small florets while the other one had terminal clusters spike inflorescence . Stamens were three in first species with short filament while they were 2-3 stamens with long filament in the other one. Also the study determined the rat of the flowering period for the two species as well as the study of ecological and geographical distribution for the two species in Iraq, the results documented with pictures. It could be depended to studied traits of the plant species for classification.